AUTISTIC SPECTRUM DISORDER: PEDAGOGICAL PRACTICES FOR THE REGULAR EDUCATION ROOM - Teixeira Lima, Larissa; Rocha Lopes, Juliana; Paula Bochi, Ana; Maria Bochi Silva, Élida; Pereira Gusmão, Jacqueline; da Silva Dias, Edcler; Cristina de Oliveira Amorim Pedro, Viviane; de Souza Oliveira, Renata; Soprani Santos, Leni; Manuela Bárbara Belizário, Carla (Revista Gênero e Interdisciplinaridade, 2024)
This article is part of the conclusion of the Postgraduate Course in Special Education from Favimo University. It focuses on discussing some educational proposals aimed at students with Autistic Spectrum Disorder (ASD), which are inserted in the regular school classrooms. It is the classroom teacher who will mediate the whole of the inclusive process, he is the one who promotes the child’s initial contact with other children in the class and is responsible for including him in everyday activities. In this perspective, this theme reaffirms the need that everyone understands and accepts human diversity, and can contribute to the construction of a fairer and more egalitarian society. The article will be divided into three great moments. In the first one will be made a global contextualization of special education. Then the autistic spectrum disorder will be presented- Tea its main characteristics and needs. Finally, some pedagogical proposals that can be used in the classroom will be presented. It is concluded that a lot has changed since the beginning of history when we talk about people with ASD. Of schizophrenics there are numerous distinct characteristics even in the same disorder. Of communication difficulty to high skills. Autism is one of the syndromes as the largest variants of behavior, without modeled patterns.